2007
DOI: 10.1002/hep.21822
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1-antitrypsin mutant Z protein content in individual hepatocytes correlates with cell death in a mouse model

Abstract: Alpha-1-antitrypsin (a1AT) deficiency is caused by homozygosity for the a1AT mutant Z gene and occurs in 1 in 2000 births. The Z mutation confers an abnormal conformation on the protein, resulting in an accumulation within the endoplasmic reticulum of hepatocytes rather than appropriate secretion. The accumulation of the mutant protein is strikingly heterogeneous within the liver. Homozygous ZZ children and adults have an increased risk of chronic liver disease, which is thought to result from this variable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 21 publications
3
74
0
4
Order By: Relevance
“…Quantitative RT-PCR revealed that both groups of hepatocytes expressed similar AAT-Z mRNA levels (data not shown). In contrast, Western blot analysis showed a much higher AAT-Z content in the globulecontaining hepatocytes, which was consistent with the results of Lindblad et al, who also showed that the globule-containing cells had a higher rate of apoptosis than globule-devoid hepatocytes (15).…”
Section: Aat-z Globule-containing Hepatocytes Have Aat-z Transgene Ansupporting
confidence: 90%
“…Quantitative RT-PCR revealed that both groups of hepatocytes expressed similar AAT-Z mRNA levels (data not shown). In contrast, Western blot analysis showed a much higher AAT-Z content in the globulecontaining hepatocytes, which was consistent with the results of Lindblad et al, who also showed that the globule-containing cells had a higher rate of apoptosis than globule-devoid hepatocytes (15).…”
Section: Aat-z Globule-containing Hepatocytes Have Aat-z Transgene Ansupporting
confidence: 90%
“…42 Markers of apoptosis were found to be more pronounced in hepatocytes with greater levels of insoluble ATZ. Furthermore, stimulation of the extrinsic apoptotic pathway with antibody to fas resulted in increased apoptosis almost exclusively within the globulecontaining cells.…”
Section: Hepatic Carcinogenesis In At Deficiencymentioning
confidence: 97%
“…Indeed, the data in this recent study shows an increase in one antiapoptotic protein, cFLIP, in cells with higher levels of insoluble ATZ. 42 This would mean that the globule-devoid hepatocytes were even more resistant than normal hepatocytes to apoptosis. This is probably an important distinction because relative resistance to apoptosis in either of these cellular compartments could potentially contribute to the mechanism of carcinogenesis.…”
Section: Hepatic Carcinogenesis In At Deficiencymentioning
confidence: 99%
“…In brief, the report suggested the possibility that HERSD associated with variant fibrinogenemia might be caused by decreasing function of the autophagic pathway. Moreover, molecular mechanisms of A1AT homozygous Z mutation causing hepatocyte injury have been studied extensively and showed increased ER retention as a conformational disease [24], activation of ER-specific stress responses [25], up-regulated mitochondrial autophagy [26], or mitochondrial injury and apoptosis [27]. Our γ375W-CHO cells indicated cytoplasmic aberrant inclusion bodies with large granular or fibrous forms and this suggested that variant fibrinogen was retained and aggregated within the dilated ER.…”
Section: Discussionmentioning
confidence: 77%